Vitamins E and C Concentrations in Anaemia Subjects Attending Braithwaite Memorial Specialist Hospital Port Harcourt - George-Opuda, Ibitoroko Maureen; Adegoke, Adebayo Olugbenga; Wankasi, Miebi M; Nnatuanya, Isaac Nnamdi (International Journal of Medical and Health Sciences Research, 2020)
The study was carried out to determine Vitamins E and C concentrations in anaemic subjects attending Braithwaite memorial Specialist Hospital Port Harcourt. Three hundred (300) subjects made up of 150 anaemic patients (77 females and 73 males) age ranging between 15 – 67 years attending the Braithwaite Memorial Hospital (BMH) Port Harcourt and 150 apparently normal healthy individuals (78 females and 72 males) , age ranging between 15 – 67 years were used as controls for this study. The subjects had their Haemoglobin, Vitamins E and C concentrations determined. The results were subjected to statistical analysis using Statistical Package for Social Sciences (SPSS) 22. The result of the study showed that there was significant difference (P <0.05) in haemoglobin concentrations (g/dl) of 13.51±1.14 in healthy subjects compared with 6.77±1.82 in anaemic subjects as shown in Table 1 below. Also the Vitamin E concentration (Mg/l) of 7.82±2.38 was significantly different from 5.33±1.90 in anaemic subjects (P <0.05). The Vitamin C concentration (Mg/dl) of 0.61±0.29 was not significantly different from 0.28±0.16 in anaemic subjects (P >0.05). This study showed that there was significant decrease in Vitamin E concentrations in anaemic subjects.